An experimental study on the wind pressure distribution of tapered super high‐rise buildings. (25th June 2018) - Deng, T.; Fu, J.Y.; Xie, Z.N.; Pi, Y.L.; Shi, B.Q.
Summary: Studies on the effect of different shape strategies on wind‐induced responses of super tall buildings have been extensive. However, little systematic research on the influence of aerodynamic shapes on wind pressure distributions of super high‐rise building having a height more than 500 m is reported in the literature. In this paper, a series of wind tunnel tests are conducted on models simulating tapered buildings taller than 500 m with an aspect ratio of 9:1 by applying synchronous pressure measurement technology to investigate the influence of different shape strategies on the wind force coefficients of the cross section ( C s ) and on the peak negative pressure distributions on surfaces. The shape strategies considered include tapering of the cross section of a building along its height, chamfered modification, and opening ventilation slots. It is found that the wind force coefficient C s increase with an increase of the tapering ratio. It is shown that chamfered modification can effectively reduce most of the wind force coefficients C s to less than 0.9. As for peak wind pressures, a zone having a higher negative pressure is found to locate at the bottom of the side faces of the model. With an increase of the tapering ratio, the peak negative pressure of side faces of the model slightly decreases. Chamfered modification can significantly increase the peak negative pressure at the chamfered location. Furthermore, it is demonstrated that opening ventilation slots had less effect on C s, but the peak negative pressure can significantly increase at the area of opening ventilation slots and adjacent areas.